Recent Approach of Endocrine Function of Thyroid Gland and its Impact on Pregnancy - Faisal Alanazi (Pakistan Journal of Medical & Health Sciences, 2022)
Introductions: Pregnancy is a period in which there are physical and hormonal changes for the development of the fetus and essentials nutrients supply and the preparation of the maternal organism for birth and lactation. There is a paucity of data on the endocrine function of the thyroid gland in pregnancy in Saudi Arabia. The purpose of this study was to assess the impact of the endocrine function of thyroid gland in pregnancy and current techniques for its management. Methods: In this systematic review and meta-analysis, PRISMA (preferred reporting items for systematic review and meta-analysis) was used. Cochrane handbook guidelines were used for all aspects of this study. It includes published and unpublished studies with different study designs. Such studies were found from databases which include Google Scholar, Embase Medline, PsycINFO, Google, and Cochrane library up to the last week of January 2022 without any language restriction and identified all RCTs related to the endocrine function of the thyroid gland and its impact on pregnancy. Results: All RCTs connected to the endocrine function of the thyroid gland and its impact on pregnancy were found using a total of 304 articles from the electronic database Google Scholar, PubMed, Embase, PsycINFO, and the Cochrane Library, which were searched without any language restrictions. ’’Endocrine’’, ’’Endocrine function’’, ’’Thyroid’’, ’’TSH’’, ‘‘T3’’, ‘‘T4’’, ‘‘hormones’’ and ‘‘pregnancy’’ and ‘‘randomized controlled trial’’ were some of the search terms we utilized. In addition, we searched references in a few journals to find more potentially relevant studies. Due to redundancy, 92 articles were excluded from the total of 304. A total of 107 articles were reviewed, with 77 rejected following a preliminary review. There were 30 full-text papers reviewed for eligibility, and 10 of them met the inclusion requirements, with all of the selected articles being of high quality. The parameters of the trials differed greatly in terms of treatment length and population investigated. All of the studies were nonrandomized and compared groups based on retrospective chart reviews. Out of 10 studies, three were from Iran, two from Saudi Arabia, one from the United States, one from Denmark, one from Ireland, one from Netherland, and one from Australia. Conclusion: Thyroid diseases are the most significant endocrine dysfunction related to pregnancy; however, treatments for subclinical thyroid dysfunction are still controversial; the purpose of therapy should be to maintain euthyroidism during pregnancy. Adequate circulation of thyroid hormone levels is important for appropriate reproductive function. A greater understanding of these problems will allow practitioners to enhance the maternal and perinatal outcomes in such pregnancies. This study concludes that there is a requirement for additional research on TSH during pregnancy without instances of autoimmune thyroid dysfunction for the development of trimester-specific TSH normal range in the population of Saudi Arabia, whereas it also supports the use of TSH as a marker of pregnancy-induced hypothyroidism.